1982
DOI: 10.1139/z82-009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of forced renesting, seasonal date of laying, and female characteristics on clutch size and egg traits in captive American Kestrels

Abstract: BIRD, D. M., and P. C. LAGUE. 1982. Influence of forced renesting, seasonal date of laying, and female characteristics on clutch size and egg traits in captive American Kestrels. Can. J. Zool. 60: 71-79. Of 78 nesting attempts by captive American Kestrels (Falco sparverius) between 1974 and 1977,95% successfully renested after removal of the first clutch. Replacement clutches had fewer eggs, longer eggs, and eggs with thicker shells than first clutches. Clutch size, egg length, eggshell thickness, and fresh eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 32 publications
(26 reference statements)
1
6
0
Order By: Relevance
“…However, many studies of piscivorous, gallinaceous, and passerine birds showed no association between PCB exposure of adults and eggshell thinning (Koeman et al, 1973). In this study, eggshells of PCB eggs were not different from those of control eggs, and the thickness of shells was similar to that previously reported for this species (Bird & Laguë, 1982). In this study, eggshells of PCB eggs were not different from those of control eggs, and the thickness of shells was similar to that previously reported for this species (Bird & Laguë, 1982).…”
Section: Discussionsupporting
confidence: 90%
“…However, many studies of piscivorous, gallinaceous, and passerine birds showed no association between PCB exposure of adults and eggshell thinning (Koeman et al, 1973). In this study, eggshells of PCB eggs were not different from those of control eggs, and the thickness of shells was similar to that previously reported for this species (Bird & Laguë, 1982). In this study, eggshells of PCB eggs were not different from those of control eggs, and the thickness of shells was similar to that previously reported for this species (Bird & Laguë, 1982).…”
Section: Discussionsupporting
confidence: 90%
“…Quite simply, body size of some female kestrels, and hence likely most males (the smaller sex), may be too small for proper incubation of their modal clutch size of five eggs. The fact that egg size and female size are not correlated (see Results, andPorter andWiemeyer 1972, Bird andLague 1982) would further add to the problems of small birds during incubation. We do not know to what degree such problems might be exacerbated by cool temperatures experienced at the relatively high latitude of our study population.…”
Section: Discussionmentioning
confidence: 97%
“…In the vast majority of single-brooded species, females lay more eggs when they initiate clutches early in the season than when they initiate clutches late in the season (Klomp, 1970). The American kestrel is no exception (Bird & Laguë, 1982;. Data collected on wild, free-living American kestrels over three breeding seasons revealed that females initiating clutches early in the season tend to lay five-or six-egg clutches, whereas those initiating clutches late in the season tend to lay four-eggs or fewer .…”
Section: Determinants Of Reproductive Effortmentioning
confidence: 99%